Brief research report: Chest radiographic thoracic area in term ventilated infants without respiratory disease - Theodore Dassios; Theodore Dassios; John Adu; Anne Greenough; Anne Greenough (Frontiers Media S.A., 2023)
ObjectiveTo report values of the chest radiographic thoracic area (CRTA) in ventilated, term-born infants without respiratory disease and to evaluate whether CRTA is related to demographic data at birth.MethodsRetrospective, observational cohort study in a tertiary neonatal unit at King's College Hospital NHS Foundation Trust, London, UK.Newborn infants born after 36 completed weeks of gestation, ventilated for poor perinatal adaptation or hypoxic ischaemic encephalopathy without respiratory disease and admitted in a recent eight-year period (2014-2022).The CRTA was assessed by free-hand tracing of the perimeter of the thoracic area as outlined by the diaphragm and the rib cage excluding the mediastinal structures and was calculated using the Sectra PACS software.ResultsOne hundred and twenty-one infants (75 male) were included with a median (IQR) gestation of 40 (38-41) weeks and birth weight of 3.41 (3.04-3.75) kg. The median (IQR) CRTA was 2,589 (2,167-2,943) mm2 and was significantly related to birth weight (r = 0.316, p = 0.003), gestation at birth (r = 0.193, p = 0.032) and birth weight z-score (r = 0.187, p = 0.038).ConclusionsWe report values of the chest radiographic thoracic area in ventilated term-born infants which could be used as reference for determining respiratory disease severity.